INSURANCE INTEREST IN THE PERSONAL INSURANCE - Svintradze, Ketevan (European Scientific Journal, ESJ, 2013)
Insurance, which was created in the early centuries, is of great interest even today. As a result, private insurance had to be distinguished. A great part of society is interested in protecting property. The basic of insurance must be juridical connection of subjects and people that was called insurance title. In the conditions of modern life, it is necessary for a person to be insured.